Effects of a Specialist‐Led, School Physical Education Program on Bone Mass, Structure, and Strength in Primary School Children: A 4‐Year Cluster Randomized Controlled Trial. (3rd September 2015) - Daly, Robin M; Ducher, Gaele; Hill, Briony; Telford, Rohan M; Eser, Prisca; Naughton, Geraldine; Seibel, Markus J; Telford, Richard D
ABSTRACT: This 4‐year cluster randomized controlled trial of 365 boys and 362 girls (mean age 8.1 ± 0.3 years) from grade 2 in 29 primary schools investigated the effects of a specialist‐taught physical education (PE) program on bone strength and body composition. All children received 150 min/week of common practice (CP) PE from general classroom teachers but in 13 schools 100 min/week of CP PE was replaced by specialized‐led PE (SPE) by teachers who emphasized more vigorous exercise/games combined with static and dynamic postural activities involving muscle strength. Outcome measures assessed in grades 2, 4, and 6 included: total body bone mineral content (BMC), lean mass (LM), and fat mass (FM) by DXA, and radius and tibia (4% and 66% sites) bone structure, volumetric density and strength, and muscle cross‐sectional area (CSA) by pQCT. After 4‐years, gains in total body BMC, FM, and muscle CSA were similar between the groups in both sexes, but girls in the SPE group experienced a greater gain in total body LM (mean 1.0 kg; 95% CI, 0.2 to 1.9 kg). Compared to CP, girls in the SPE group also had greater gains in cortical area (CoA) and cortical thickness (CoTh) at the mid‐tibia (CoA, 5.0% [95% CI, 0.2% to 1.9%]; CoTh, 7.5% [95% CI, 2.4% to 12.6%]) and mid‐radius (CoA, 9.3% [95% CI, 3.5% to 15.1%]; CoTh, 14.4% [95% CI, 6.1% to 22.7%]), whereas SPE boys had a 5.2% (95% CI, 0.4% to 10.0%) greater gain in mid‐tibia CoTh. These benefits were due to reduced endocortical expansion. There were no significant benefits of SPE on total bone area, cortical density or bone strength at the mid‐shaft sites, nor any appreciable effects at the distal skeletal sites. This study indicates that a specialist‐led school‐based PE program improves cortical bone structure, due to reduced endocortical expansion. This finding challenges the notion that periosteal apposition is the predominant response of bone to loading during the prepubertal and early‐pubertal period. © 2015 American Society for Bone and Mineral Research.